Differential reactions of urban and rural teachers to blended learning: evidence from Chinese secondary schools - Wang, Lin; Omar, Muhd Khaizer; Zakaria, Noor Syamilah; Zulkifli, Nurul Nadwa (IGI Global, 2024)
The COVID-19 pandemic has provided an opportunity for implementing blended learning in Chinese secondary schools. However, teachers have encountered several problems and challenges with the new pedagogical paradigm. Therefore, this study aims to identify the factors influencing the implementation of blended learning in urban and rural secondary schools from the perspective of secondary school teachers and to examine the teachers’ different responses to these factors. Interview data were collected from 13 secondary school teachers in Guangdong Province, China. The findings identify seven factors influencing the implementation of blended learning from the teachers’ perspective, including blended learning curriculum design, teaching resources, teaching ability, teacher-student interactive behavior, teacher motivation, students’ ability, and workload. The distinct differences between urban and rural teachers’ responses to the aforementioned influential factors provide a reference for the government and schools to establish a moderating mechanism for blended learning implementation.